Ionospheric current systems on days of low equatorial ΔH - Alex, S.; Kadam, B.D.; Rao, D.R.K. (My University, 1998)
Examination of the day to day variability in the equatorial electrojet strength, in the Indian region, shows that certain quiet days (Ap ≤ 6) are characterized by an abnormally low magnitude of the jet strength. Geomagnetic field data (H-component) on these abnormal jet days along with the normal jet days from equatorial and low latitude stations are subjected to the statistical methodology of Principal Component Analysis. Results suggest that the contributions to the diurnal variations on such abnormal days could be accounted for by an additional noon-time field. The contributing factors for the observed spatial distribution of the additional fields that are responsible for the changes in low latitude dynamo currents are discussed.
Keywords: Eigen vector; Geomagnetic field; Equatorial electrojet